The Performance of Fibre Reinforced Polymer Strengthening in the Fire - Stratford, Tim J; Gillie, Martin; Chen, J (The University of Edinburgh, 2007)
Bonded fibre-reinforced-polymer (FRP) strengthening is an increasingly popular refurbishment method. This involves gluing an advanced fibre composite on to the existing structure to increase its sectional capacity. One issue that has yet to be fully addressed is the fire performance of bonded FRP strengthening. The opportunity was taken to evaluate the performance of bonded FRP in Dalmarnock Test One.
Chapter 9 in the book: The Dalmarnock Fire Tests: Experiments and Modelling, Edited by G. Rein, C. Abecassis Empis and R. Carvel, Published by the School of Engineering and Electronics, University of Edinburgh, 2007. ISBN 978-0-9557497-0-4
Keywords: Dalmarnock; Experiment